PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN MEDAENG, SURABAYA YANG DILAKUKAN OLEH LEMBAGA YDSF DENGAN MEMBERDAYAKAN DANA INFAQ - Boby Ardyan Muhammad; Tika Widiastuti (Universitas Airlangga, 2019)
The purpose of this research is to acknowledge the utilization of Yayasan Dana Sosial Al Falah’s (YDSF) infaq funds and inmates empowerment at Medaeng Correctional Facility. The motive behind this research is the phenomenon of inmates empowerment in Medaeng Correctional Facility that is done by YDSF by utilizing infaq funds. Empowerment is purposed to develop inmates to become a better person in behavior, spiritual, and social connection. This is a qualitative research. The approach of this research is using case study method. Informants in this research is YDSF, correctional facility staffs, and inmates. Data gathering technique is done by data reduction, data presentation, and data conclusion. Findings in this research show that infaq utilization affect da’wah aspect which is inmates empowerment in Medaeng correctional facility. This is not only develops inmates to become a better person, but also their spirituality and religion activity so when they done their time, they’ll be easily accepted by the people.Keywords: infaq, Empowerment, DevelopmentREFERENCES Bably, Muhammad. M. 1990. Kedudukan Harta Menurut Pandangan Islam.Terj. Abdul Idris. Jakarta.Hafidhuddin, D. 1998. Panduan Praktis tentang Zakat, Infaq, dan Shadaqah.Jakarta: gema Insani.Mardany. 2012. Fiqh Mu’amalah. Jakarta: Kencana Media Group.Priliyanti, Indah. 2010. Transformasi Tradisi Filantropi Islam : Studi Model Pendayagunaan Zakat, Infaq, sadaqah, Wakaf di indonesia. Jurnal Economica. No. 11/ Edisi II/ November 2010.Mustofa, Muhammad. 2007. Kriminologi kajian sosiologi terhadap kriminalitas perilaku menyimpang dan pelanggaran hukum. Depok: FISIP UI Press.Direktorat Jenderal LAPAS. 2008. Cetak biru pembaharuan pelaksanaan sistem LAPAS. Jakarta: Departemen Hukum dan Hak Asasi Manusia Direktorat Jenderal LAPAS.Direktorat Jendral Pemasyarakatan, 2009:11Teuku A, 2017. Peran Pemberdayaan Dana Zakat, Infaq dan Shadaqah Dalam Bidang Pendidikan (studi kasus: Yayasan Dana Sosial Al-Falah dan Rumah Kepemimpinan Surabaya).Skripsi. Tidak Diterbitkan. Fakultas Ekonomi dan Bisnis. Universitas Airlangga. Moloeng, Lexy. 2012. Metodologi Penelitian Kualitatif. Jakarta. Remaja Rosdakarya Sugiyono. 2011. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: AfabetaSugiyono. 2012. Metode Penelitian Kuantitatif, kualitatif dan R & D. Bandung. Alfabeta.Miles, M.B., dan Michael Huberman. 2009. Analisis Data Kualitatif Buku Sumber Tentang Metode-Metode Baru. Jakarta. UI Press.Peraturan Perundang-undangan:Undang-Undang No. 12 Tahun 1995 tentang PemasyarakatanPeraturan Pemerintah No. 31 Tahun 1999 tentang Pembinaan dan Pembimbingan Warga Binaan Pemasyarakatan.